THE EFFECTIVENESS OF AN INTERACTIVE DIGITAL MODULE BASED ON GAMIFICATION IN ENHANCING JUNIOR HIGH SCHOOL STUDENTS’ VOCABULARY LEARNING MOTIVATION - Muhamad Khoerul Hadits; M.Pd., Al Juska Sasni Akbar; Muhamad Ichsan Nurjam'an; Lucky Dewanti (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2026)
This study aims to develop and evaluate the effectiveness of an interactive digital module based on gamification to enhance seventh-grade students’ vocabulary learning interest and achievement at SMPN 2 Leuwisadeng. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Students’ perception was measured through three indicators—motivation, engagement, and grit—using a Likert-scale questionnaire. The results indicate that all three indicators fall within the moderately high to high categories, demonstrating that the gamified module successfully increased students’ interest in learning English vocabulary. In terms of cognitive performance, the pre-test and post-test results show a significant improvement, with the mean score increasing from 51.54 to 71.83. A paired samples t-test revealed a significance value of p < 0.001, confirming that the interactive digital module had a substantial impact on students’ vocabulary mastery. Overall, the findings suggest that the gamification-based interactive digital module is effective in improving both students’ learning interest and vocabulary achievement and can serve as an innovative alternative for English language instruction at the junior high school level.